Cuestiones actuales de la didáctica de las ciencias físicas en Francia : observaciones comparativas - Martinand, J.L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The aim of this paper is to draw a first inventory of coincidences and differences of theoretical output between science and mathematics education. A comprehensive analysis of the origin and meaning of both coincidences and divergences is made.